STUDY OF TOEIC PREDICTION TEST RESULTS AS AN INDICATOR OF VOCATIONAL HIGH SCHOOL STUDENTS’ WORK READINESS: A CASE STUDY AT SMKN 3 JAKARTA - Redjeki Agoestyowati; Umi Hanik Makmuroh (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to analyze the results of the TOEIC Prediction Test as an indicator of work readiness for vocational high school students, especially at SMKN 3 Jakarta. TOEIC (Test of English for International Communication) is a measuring tool for English language proficiency that is often used as a requirement by the industrial world and the world of work. This study uses a quantitative descriptive approach with data from 213 grade XII students who took the TOEIC Prediction Test. The results showed that most students were at an intermediate level, with the following score details: above 800 (3.3%), 700–799 (8.96%), 600–699 (16.51%), 500–599 (28.77%), 400–499 (21.70%), 300–399 (9.91%), 200–299 (8.96%), and 100–199 (1.89%). These data indicate that most students still need to improve their English skills to meet professional communication standards in the world of work.